Structural basis for different types of hetero-tetrameric light-harvesting complexes in a diatom PSII-FCPII supercomplex - Ryo Nagao; Koji Kato; Minoru Kumazawa; Kentaro Ifuku; Makio Yokono; Takehiro Suzuki; Naoshi Dohmae; Fusamichi Akita; Seiji Akimoto; Naoyuki Miyazaki; Jian-Ren Shen (Nature Communications, 2022)
Fucoxanthin chlorophyll a/c-binding proteins (FCPs) harvest light energy in diatoms. The authors analyzed a structure of PSII-FCPII supercomplex at high resolution by cryo-EM, which identified each FCP subunit and pigment network in the supercomplex.